Wild Rosa L. and Crataegus L. taxa of the Middle Noteć River Valley (NW Poland) - Sołtys-Lelek, Anna; Gruszka, Wojciech (Biodiversity: Research and Conservation, 2020)
This paper presents a study on the distribution of hawthorns and wild roses of the Middle Noteć River Valley region in north-west (NW) Poland. The main purpose of the study was to provide a full list of wild Crataegus and Rosa taxa growing in the examined area. Field studies (2016-2017) and formerly published data, made it possible to recognize 10 taxa (including one rose hybrid within the rank of species). Four new taxa were found in the explored area during studies. These were: Crataegus rhipidophylla Gand., C. ×macrocarpa Hegetschw., C. ×subsphaericea Gand. and Rosa ×subcanina (H. Christ) Vuk.